2023
DOI: 10.3389/fpubh.2023.1120596
|View full text |Cite
|
Sign up to set email alerts
|

Research on patient-centered design for post-stroke depression patients based on SEM and comprehensive evaluation

Abstract: IntroductionSince COVID-19, medical resources have been tight, making it inconvenient to go offline for the sequelae of diseases such as post-stroke depression (PSD) that require long-term follow-up. As a new digital therapy, VRTL began to gain popularity.MethodThe research is divided into two parts: pre-test and post-test. In the pre-test, an evaluation method integrating reality-based interaction (RBI), structural equation model (SEM), analytic hierarchy process (AHP), and entropy weight method is proposed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Stroke-related depression is a well-known issue that can significantly impact stroke patients’ prognosis ( 33 ). The current study demonstrated that psychological disorders played a mediating role in the association between dysphagia and QOL.…”
Section: Discussionmentioning
confidence: 99%
“…Stroke-related depression is a well-known issue that can significantly impact stroke patients’ prognosis ( 33 ). The current study demonstrated that psychological disorders played a mediating role in the association between dysphagia and QOL.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, societal issues involve low willingness of patients to choose community primary care and insufficient information reception, among others. 14 However, the existing digital health literature primarily delves into clinical applications and electronic healthcare, 15 such as the application of machine learning (ML)/deep learning (DL) technologies in various medical fields, 16 for instance, the use of virtual reality rehabilitation landscape (VRTL) technology in clinical treatment, 17 and the design and application of clinical decision support systems and electronic nursing records. 18 The purpose of this article is to explore the construction of an information-based bidirectional referral mechanism within the framework of a healthcare alliance model.…”
Section: Introductionmentioning
confidence: 99%
“…With stroke, patients often have different degrees of motor impairment, making it difficult to walk and reintegrate into society and negatively affecting their physical and mental health ( 7 ). There are few studies on the social alienation of patients with stroke, most of which focus on the negative emotions and motor impairment caused by stroke ( 8 , 9 ). Therefore, it is essential to investigate the social alienation of patients with stroke and explore its potential mechanism to help patients better adapt to society.…”
Section: Introductionmentioning
confidence: 99%